Perspectives on urban conditions and population health - David Vlahov; Sandro Galea; Emily Gibble; Nicholas Freudenberg
The majority of the world's population will live in cities in the next few years and the pace of urbanization worldwide will continue to accelerate over the coming decades. While the number of megacities is projected to increase, the largest population growth is expected to be in cities of less than one million people. Such a dramatic demographic shift can be expected to have an impact on population health. Although there has been historic interest in how city living affects health, a cogent framework that enables systematic study of urban health across time and place has yet to emerge. Four alternate but complementary approaches to the study of urban health today are presented (urban health penalty, urban health advantage, urban sprawl, and an integrative urban conditions model) followed by three key questions that may help guide the study and practice of urban health in coming decades.